An Exploratory Investigation Into Women's Experience of Sexual Harassment in the Workplace - Spiliopoulou, Ashleigh (Violence against women, 2023)
The recent surge in online movements challenging the culture of silence surrounding sexual harassment has created new spaces for women to share their stories. This research employed a qualitative, exploratory design to study 199 comments on a public online community forum: “What's The Wildest Thing That Happened To You As A Working Woman?”. Inductive thematic analysis was performed on the data which resulted in three overarching themes: “a harassment endemic,” “the (im)balance of power,” and “it's in the culture”. Sexual harassment was centered as a normal part of women's workplace experience, as was lack of affirmative action from employers which increased the severity of experiences. Organizations must commit to challenging the structures and individuals that perpetuate unsafe working conditions for women.